Pengaruh Kemampuan, Motivasi dan Komunikasi Organisasi Terhadap Kinerja Pegawai Kantor Badan Pertanahan Nasional Kabupaten Buleleng - Widyawati, Kadek Ayu Dina; Suwendra , I Wayan (Universitas Pendidikan Ganesha, 2024)
This research intends to determine the effect of ability, motivation, and organizational communication on the performance of BPN Buleleng employees. This research is classified into the type of causal research. The number of samples used in this research is 103 respondents. The data collection method used in this research is a questionnaire. This research uses multiple linear regression analysis methods, namely covering the t test and F test with the help of SPSS For Windows Version 2. The results of this research show that there is a positive and significant influence between ability, motivation, and organizational communication on the performance of BPN Buleleng regency with a significance value of 0.000 < 0.05; Ho is rejected. Ability, motivation, and organizational communication have an influence of 71.2% on the performance of employees of the Buleleng Regency BPN Office, as evidenced by a coefficient of determination of 0.712.